2015
DOI: 10.1177/1059840515620281
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses’ Experiences of Managing Young People With Mental Health Problems

Abstract: Prevalence of mental health disorder is increasing among young people. It is recognized that early intervention is essential in supporting young people, and care provided within schools to support emotional well-being is recommended as part of this process. A scoping review was undertaken examining school nurses' experiences of supporting the mental health of schoolchildren. Findings suggest that school nurses have a central role in supporting young peoples' mental health, although a number of barriers exist w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 38 publications
4
39
1
Order By: Relevance
“…The survey shows that school nurses are more satisfied with the competence they have in primary prevention work/health promotion than with their competence in the field of mental health (Wessel Andersson, Osborg Ose, & Norvoll, ). This lack of confidence regarding mental health issues is also described in UK studies (Haddad, Butler, & Tylee, ; Pryjmachuk et al., ; Ravenna & Cleaver, ).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The survey shows that school nurses are more satisfied with the competence they have in primary prevention work/health promotion than with their competence in the field of mental health (Wessel Andersson, Osborg Ose, & Norvoll, ). This lack of confidence regarding mental health issues is also described in UK studies (Haddad, Butler, & Tylee, ; Pryjmachuk et al., ; Ravenna & Cleaver, ).…”
Section: Introductionmentioning
confidence: 68%
“…& Norvoll, 2006). This lack of confidence regarding mental health issues is also described in UK studies (Haddad, Butler, & Tylee, 2010;Pryjmachuk et al, 2012;Ravenna & Cleaver, 2016 among adolescents .…”
mentioning
confidence: 84%
“…More broadly, the attention to TC as an important determinant of health calls for greater collaboration between the public health and educational sectors. With the potential of student–teacher interactions as protective for risk behaviours 15 17 and the emerging concerns about mental health among youth, 49 , 50 the role of education systems as public health institutions and as sites for public health interventions become vitally important. It is therefore fundamental that public health adopts a more nuanced understanding of the elements within schools that operate as determinants of health and the links between them.…”
Section: Discussionmentioning
confidence: 99%
“…However, their general responses indicated that they paid most attention to those in most need of their help, due to their heavy workloads. If so, the nurses’ prioritization, which may be influenced by gender stereotypes, may exacerbate problems associated with resource limitations and the organization of health services [23, 42]. …”
Section: Discussionmentioning
confidence: 99%